Collisions between liquid droplets during the intersection of aerosol flows in a heated gas. (1st September 2022) - Tkachenko, P.P.; Shlegel, N.E.; Strizhak, P.A.
Graphical abstract: Highlights: A rise in the gas temperature led to an increase in the number of secondary fragments. At T g  = 300–400 °C droplets with r d  = 0.075–0.1 mm prevail. A temperature rise contributed to a 2–3 times increase in area ratios S 1 / S 0. At T g  = 100–400 °C, droplets increased in size due to expansion of liquid on heating. The motion of droplets in a heated gas led to a 10–30% change in their size due to evaporation. Abstract: The paper presents the experimental findings on the water droplet collision behavior during the intersection of two aerosol flows in a high-temperature gas environment. Aerosol flows were produced by two strip pattern nozzles angled at 45° towards each other in the same plane. The resulting flow had an opening angle of 60°. The droplet impact angle (αd ) was varied from 0 to 90°, droplet radii ( R d1, R d2 ) from 0.1 to 1.2 mm, and droplet velocities ( U d1, U d2 ) from 2 to 12 m/s. The gas temperature in the droplet collision zone was varied using an induction heater with an internal volume of about 0.13 m 3 with viewing windows to record the key parameters (number, size, velocities, and trajectories) of liquid fragments before and after collision. The air temperature ranged from 20 to 400 °C in the experiments. Using a high-speed video camera, we recorded four collision regimes: coalescence, separation, disruption, and bounce. We also identified the main differences in the number and size of secondary droplets formed in an aerosol flow after the collision of two primary ones. A temperature rise led to an increase in the number of secondary fragments. The size distributions of secondary fragments are presented for three ranges of size ratios of initial droplets: Δ < 0.3; 0.3 < Δ < 0.7; Δ > 0.7. The impact of droplet collisions on their size variation rates was estimated at the gas temperature T g  = 20–400 °C. Finally, we compared the contribution of this factor and evaporation without droplet-droplet collisions.